Experimental analysis of the effect of nitrogen gas on the H2S stripping process during the pigging operation of a long crude oil pipeline. (December 2020) - Zheng, Dengfeng; Jiang, Zhongan; Shi, Jihao; Wang, Yapeng; Liu, Zhenyi
Abstract: Hydrogen sulfide (H2S) precipitation incidents often occur during pigging operations in crude oil pipelines, which result in the leakage of H2S with a high concentration at the site and seriously threaten the life and health of workers. To identify the main cause of H2S precipitation, this study designs a crude oil pipeline experimental system by which pigging operations could be simulated according to the on-site pipeline configuration. In addition, this paper determines the conditions at which a large amount of H2S could be stripped in an elbow pipeline when N2 passes through the pig to contact the oil sample and pushes to return the oil compared with those in a straight pipeline. Furthermore, this paper analyzes the effect of the N2 injection rate on H2S precipitation under repeated N2 contact with oil samples. Finally, this paper develops an empirical formula presenting the relationship among the H2S concentration ratio and its various influencing factors, which could give immediate guidance to prevent the occurrence of similar accidents.